TRAINING ORGANIZATIONAL TRAINERS TO FRAME FEEDBACK: MITIGATING FACE CONCERNS AND SUPPRESSING EGO DEFENSIVENESS - Arterburn, Elissa (My University, 2015)
This dissertation applies Implicit Person Theory (IPT) to the contexts of organizational training and feedback. IPT scholars argue that individuals ascribe to one of two groups regarding perceptions of ability: entity or incremental theorists. Entity theorists believe abilities are fixed, and constant; incremental theorists believe abilities are malleable, and subject to development. This study seeks to demonstrate how organizational feedback processes can be framed strategically to maximize learning, including the skills-based learning needed for successful operation in high-reliability organization (HRO) training and non-HRO training. Data were collected at two sites: an anesthesiology department and a communication department at a large southwestern university. Using an experimental design, the researcher hypothesized that growth mindset training would influence the quality of trainers’ feedback messaging, and subsequently, trainees’ learning outcomes as measured by the following dependent variables: task performance, affective learning (McCroskey, 1994), learner motivation (Richmond, 1990), perceived face threat (Cupach & Carson, 2002), and quality of feedback (Steelman, Levy, & Snell, 2004). This dissertation develops the extant IPT literature in three main ways: First, the study moved IPT training into the organizational training communication domain by emphasizing the social, not just psychological, dynamics of learning. Second, the research identified that framing organizational feedback using incremental language might violate trainees’ expectations and scripts about how feedback interactions should unfold sequentially and have unexpected consequences on learning outcomes as a result. Third, the dissertation illuminated the role that explicit discussion of theory may have on successful IPT manipulations.
Keywords: Organizational Communication